2020
DOI: 10.1007/s10853-020-04397-w
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pulverization methods on the microstructure of stiff, ductile, and flexible carbon aerogels

Abstract: Carbon aerogels find application in many fields. In most of the applications, they are used as powders and thus need to be pulverized. However, the pulverization could induce various changes in the microstructure of carbon aerogels. The extent of changes depends not only on the dominant forces of used technique, but also on the mechanical and structural properties of initial monolithic samples. In the present work, we discuss the influence of grinding, milling in shaker cryo-mill, and planetary ball mill on st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…It is interesting to note that this trend is in accordance with results reported by Schwan et al., who observed that the mesopore volume of ductile carbon aerogels increased after dry milling, while the mesopore volume of stiff carbon aerogels remained nearly unchanged. [ 17 ] In our case, we can conclude that stiffer and more rigid biopolymer fibers of alcogels are better able to withstand the friction forces in the wet milling process than the more flexible fibers of hydrogels, which are comparably easily deformed.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…It is interesting to note that this trend is in accordance with results reported by Schwan et al., who observed that the mesopore volume of ductile carbon aerogels increased after dry milling, while the mesopore volume of stiff carbon aerogels remained nearly unchanged. [ 17 ] In our case, we can conclude that stiffer and more rigid biopolymer fibers of alcogels are better able to withstand the friction forces in the wet milling process than the more flexible fibers of hydrogels, which are comparably easily deformed.…”
Section: Resultsmentioning
confidence: 59%
“…Principally, milling of gels is feasible at any step of the aerogel production: in dry aerogel‐ as well as wet alco‐ and hydrogel state. Since the application of friction and shearing forces on carbon‐ and silica gels results in relatively easy breakup due to their brittle and stiff nature, milling in dry aerogel state may be a preferred approach for these material classes: grinding of carbon and silica aerogels has been carried out via manual mortar grinding, ultrasonic‐, shaking‐, and ball‐milling processes, [ 16–18 ] among others. Depending on the milling process and applied forces, changes of the microstructure can occur, which depend on the amount of introduced energy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CZA-ZrO 2 /SO 4 bifunctional composite catalysts were prepared by the physical mixing of aerogel or xerogel sulfated zirconia (calcined at T = 300 • C) with the CZA solid in a mass ratio of 1:2. It is well known that the characteristics of bifunctional catalysts are highly dependent on the mixing process (manual grinding with mortar, agitation, ultrasound, or balls) and the applied forces [26,27]. Thus, to avoid changes of the catalyst surface properties, both of the solids were mixed in agate mortar for a short time (5 min) and without hard pressing to form the homogenous mixture.…”
Section: Preparation Of Cza-zro 2 /So 4 Bifunctional Composite Catalystsmentioning
confidence: 99%
“…Hence, structural elements, including variations in the geometry of the network forming entities down to the nanoscale, can be differentiated. These differences in fine structure are related to the chemical composition of the source material(s) and the conditions of gel syntheses [ 13 , 14 , 15 , 16 ]. The archetypes of aerogels (silica, cellulose, alginate, polyurea, etc.)…”
Section: Introductionmentioning
confidence: 99%